Physico-chemical properties of indigenous micro organism-composts and humic acid prepared from selected agro-industrial residues - Awing, Norida Hanim; Nik Ab. Majid, Nik Muhamad; Ahmed, Osumanu Haruna; Kasim, Susilawati; Ahmad, Khairulmazmi (Academic Journals, 2012)
Paddy husk (PH) and corn stalks (CS) residues are managed through burning. Besides contributing to environmental pollution, burning causes loss of vegetation cover, erosion, run off and loss of organic matter. In order to minimize this problem, a study was conducted to manage PH and CS residues through composting and to determine the physical and chemical properties of different composts and humic acid extracted from the final product. The study had six treatments namely: (T1) indigenous microorganisms (IMOIV)Steamed white rice (SWR)(30%)+PH (40%)+Chicken Dung (30%), (T2) SWR (30%)+CS (40%)+Chicken Dung (30%), (T3) IMOIVAerated Fish Pond Water (AFPW)(30%)+Paddy husk (40%)+Chicken Dung(30%), (T4) IMOIV AFPW (30%)+CS (40%)+Chicken Dung(30%), (T5) IMOIVKitchen Waste(KW)(30%)+PH (40%)+Chicken Dung (30%) and (T6) IMOIV KW (30%)+CS (40%)+Chicken Dung (30%). Composting was conducted in a white polystyrene box with a size of 30 x 15 x 25 cm. The composts produced in this study were analyzed for C:N and C:P ratio, pH (H2O and KCl), nutrients, heavy metals, organic carbon, organic matter, ash, cation exchange capacity (CEC), humic acid (HAs) and total microbial count. The HAs were evaluated for elemental composition, acidic functional groups, E4/E6 ratio and spectral characteristics using standard procedures. Results show that all IMO-composts were granular, dark brown in colour without foul odour and attained an ambient temperature at 34 days of composting indicating the stable nature of the composts. The number of bacteria and filamentous fungi involved during composting decreased at the end of the all treatments. The E4/E6, acidic functional groups; carboxyl-COOH, phenolic-OH and total acidity of the compost were consistent with the standard range. IMO-compost from CS had better quality (chemical characteristics) compared to that of paddy husk. High quality compost could be produced from CS.